A honeybee's ability to learn, recognize, and discriminate odors depends upon odor sampling time and concentration - Wright, Geraldine A. (2009)
Animals sample sensory stimuli for longer periods when they must perform difficult discrimination tasks, implying that the brain's ability to represent stimuli improves as a function of time. Though it is true in other senses, few studies have examined whether increasing sampling time improves olfactory discrimination. In the experiments reported here, we controlled odor sampling time with the goal of testing whether odor concentration affected a honeybee's ability to learn, recognize, and discriminate odors. We observed that increasing sampling time during conditioning and testing improved a honeybee's ability to learn, recognize, and differentiate low concentration (0.0002M) odors. For intermediate (0.02M) concentration odors, both acquisition and recognition improved when stimulus duration was longer, but discrimination was unaffected. Having longer to sample a high concentration (2.0M) stimulus also improved acquisition, but it did not affect the ability to recognize or differentiate odors. Differences in the time taken to respond to the conditioned and novel odors during the test period depended upon the difficulty of the discrimination task. Our results suggest that the sensory coding of molecular identity takes longer for low concentration odors.